2019
DOI: 10.21451/1984-3143-ar2019-0025
|View full text |Cite
|
Sign up to set email alerts
|

Echotextural characteristics of the mammary gland during early lactation in two breeds of sheep varying in milk yields

Abstract: The main goal of this preliminary study was to determine and compare ultrasonographic characteristics of the mammary gland in two genotypes of ewes varying in milk productivity at 2, 3 and 4 weeks after lambing. Ultrasonographic images of the udder were obtained using the 5.0-and 7.5-MHz transducers, in axial and coronal planes, in four low milk-yielding Polish Mountain sheep and six high milk-yielding Olkuska ewes. All ultrasonograms were subjected to computerized image analyses using commercially available i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 18 publications
3
8
2
Order By: Relevance
“…Mammary gland NPVs and PSDs were significantly greater after than before milking, which is in complete agreement with our earlier observations in low-and high-milk yielding sheep [13]. It is evident that the removal of the hypoechoic excretory product during complete milking alters the echotexture of the mammary parenchyma [19].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Mammary gland NPVs and PSDs were significantly greater after than before milking, which is in complete agreement with our earlier observations in low-and high-milk yielding sheep [13]. It is evident that the removal of the hypoechoic excretory product during complete milking alters the echotexture of the mammary parenchyma [19].…”
Section: Discussionsupporting
confidence: 92%
“…One year later, a personal computer-based image analytical software, named USOFT, was developed to determine the percentage of intramuscular fat in live animals [27], but subsequently it has also been shown that USOFT software could accurately interpret the scanning results only in the range of 2-8% of intramuscular fat content [28]. It has recently been suggested that variations in milk yields and chemical composition between different genotypes of sheep may contribute to the differences in echotextural attributes of the mammary gland in lactating ewes [13]. In the present study, echotextural variables of the mammary parenchyma in cows, determined mainly in the sagittal plane, were significantly correlated with protein and lactose during both milking periods, with freezing point depression in the morning and casein and solids non-fat in the evening.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The only chemical constituent that was signi cantly correlated with echotextural variables was moisture. The latter contrasts with earlier ultrasonographic studies of the pectoral muscles in broiler chickens [21] and different mammalian organs/tissues [47,48] where signi cant correlations were consistently seen between rst order echotextural variables and fat/protein content. Although the fact that turkey meat is less fatty than that of other livestock species may explain a lack of correlations with crude fat content, a reason for a lack of signi cant correlations with crude protein content remains unknown.…”
Section: Discussioncontrasting
confidence: 99%
“…The present results suggest that there were no carry-over effects of increased growth rates between weaning and breeding at seven months of age on the morphology and dimensions of the internal structures of the mammary gland of two-year-old ewes. Ultrasound imaging, however, enables only the udder dimensions to be visualised [15,22] and echo-textural characteristics [28,29] of the mammary internal structures to be assessed. Further investigations may be warranted to determine the effect of increasing growth rates prior to the first breeding on the cellular development and function of the ewe mammary gland, particularly if greater live weight differences than seen in the present experiment can be achieved.…”
Section: Difference Between Treatments and Pregnancy Rankmentioning
confidence: 99%